Design of Monitoring Lighting Counter Based on Android Application (Case Study at Tower BTS INDOSAT OOREDOO Site Utara Jepara 14JPA010) - Deki Renjaka Ardiyanto; Jenny Putri Hapsari; Eka Nuryanto Budisusila (Universitas Islam Sultan Agung, 2022)
The need for information through a monitoring system on BTS tower equipment is very necessary, including monitoring lightning strike protection. To find out whether there is a strike on the BTS, usually, technicians have to come to the BTS location to see the impact of the strike in the form of damage to the arrester, or other damage and even seek information from residents around the BTS location. The location of the BTS location is far from the head office, of course this is not effective.This research is the development of a counter lighting system designed to monitor and detect lightning strikes from a distance. By using Arduino Uno, ethernet shield, current sensor and android smart phone. The information displayed on the android smart phone is the location of the BTS tower, the time and magnitude of the strike current. The lighting protection monitoring tool based on android operation using the PZEM-004T module is a system designed and utilized to read the presence of lightning strikes which include the current flowing in the BTS tower grounding system.The test results show that the lighting protection monitoring tool using the PZEM-004T module can measure and display the current value and when a strike occurs, in real time and stored in the database. Based on the test results, it can be concluded that the results of the design of the lighting protection monitoring tool have a deviation (error) of 9,64% and a current of 12,5%.